تغطية انتفاضة القدس في القنوات الفلسطينية من وجهة نظر النخبة الإعلامية - أشتيوي، محمد محمد (دار الأطروحة للنشر العلمي, 2020)
هدفت هذه الدراسة إلى معرفة كيفية التغطية الإعلامية لانتفاضة القدس عام 2015 في الفضائيات الفلسطينية، والعوامل التي أثرت في مهنية وموضوعية هذه الفضائيات. ولتحقيق هذا الهدف اتبع الباحث المنهج الوصفي التحليلي من خلال جمع الحقائق ومحاولة تفسيرها وتحليلها. واشتملت عينة الدراسة على 120 إعلاميا من النخبة الإعلامية الفلسطينية تم اختيارهم بالطريقة العشوائية القصدية البسيطة، من المسجلين في نقابة الصحفيين الفلسطينية. وخلصت الدراسة إلى أن اتجاهات النخبة الإعلامية والسياسية نحو القنوات الفضائية الفلسطينية إيجابي، وتعتمد النخبة عليها كمصدر للمعلومات، وتعتبرها مهمة أثناء الازمات. وأن القنوات الفلسطينية ذات توجه سياسي الذي يؤثر سلبا على تغطية انتفاضة القدس. والتغطية الإعلامية للأحداث تخضع لأجندة سياسية حزبية. والسياسة التحريرية للقنوات الفلسطينية تخضع للجهة الممولة للقناة، وتدخل القيادة السياسية في عمل القناة يؤثر سلبا على الأداء. وأوصت الدراسة برفع سقف الحريات الصحفية. وعدم خضوع السياسة التحريرية للقنوات الفلسطينية للجهات الممولة. والحد من تدخل القيادة السياسية في عمل القناة الأمر الذي يؤثر سلبا على الأداء المهني.
This study goal is to explore and research the coverage of Jerusalem intifada at Palestinian TV Channels According to the viewpoint of the media elite, and how to tackle the obstacles and challenges that face it objectively. To achieve this goal the researcher followed a descriptions and analytical methodology through facts collecting of the subject and trying to interpret and analyze the facts. The study covered 120 journalists who were arbitrary picked from the media community at Journalists Syndicate. The study concluded that the opinion of the media elite towards Palestinian channels is positive, the elite depends on it as a source of information, they consider it important during crises, The Palestinian Channels are politically oriented, which negatively affects the coverage of the Jerusalem intifada, Media coverage of events is subject to a partisan political agenda. The editorial policy of the Palestinian channels is subject to funded; the interference of the political leadership in the work of the channel negatively affects performance. The study recommended increasing press freedoms, the editorial policy of the Palestinian channels is not subject to the funded parties, reducing the interference of the political leadership in the work of the channel.
Keywords: وسائل الإعلام -- القنوات الفضائية -- الإعلاميين -- إنتفاضة القدس